Enhancing Contact Pressure Uniformity in Strip Drawing Tests: A Geometric Approach to Mitigate Edge Stress Risers - Llavori Iñigo; de Argandoña Eneko Saenz; Zabala Alaitz; McClosky Alex; Uribe Maitane; Otegi Nagore (MATEC Web of Conferences)
The strip drawing test is widely used to assess the friction coefficient in sheet metal forming processes. A significant challenge in these tests is the presence of stress risers at the edges of flat punch configurations with rounded edges, which result in uneven contact pressure distributions and complicate friction characterization. To address this, a stress reliever concept involving geometric modifications is proposed. The study employed finite element simulations to explore an optimized geometry. Experimentally, two sets of die blocks—with and without stress relievers—were manufactured and tested under controlled loading conditions using a compression machine.